ANALISIS PENERAPAN MODEL-MODEL ALTERNATIF PENYEDIAAN PELAYANAN PUBLIK - Edah Jubaedah (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2011)
In order to improve the quality of public services, governments around the world try to search new arrangment in delivering public service for its peole. Conceptually and practically, there a lot of new public service arrangements that have implemented by government around the world, including in Indonesia.The main characteristic of the model of public service arrangments is that greater involvement of private sector and community in delivering public services. It assummes that government can not do by him self in delivering public services, so to improve efficiency of the public service, private sector and community should be involved. However, in implementing new model of public service arrangements, it is suggested that there are some key factors should be considered by government such as the capacity of government and private and community itself as a partner in delivering public service.